2017
DOI: 10.1111/dme.13331
|View full text |Cite
|
Sign up to set email alerts
|

Impact of accelerometer and pedometer use on physical activity and glycaemic control in people with Type 2 diabetes: a systematic review and meta‐analysis

Abstract: Background Self-directed pedometer use increases physical activity levels in the general population; however, evidence of benefit for Type 2 diabetes is unclear and has not been systematically reviewed for accelerometers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 36 publications
3
81
2
4
Order By: Relevance
“…However, a number of previous studies, including QUI et al [1], disagree with this finding. Both that study [1] and a meta-analysis in patients with type 2 diabetes [41] have shown no significant differences between accelerometers and pedometers. Consideration must be made in relation to these comparisons being indirect, with such confirmation potentially required through a future 1 versus 1 design.…”
Section: Interpretation Of the Resultsmentioning
confidence: 87%
“…However, a number of previous studies, including QUI et al [1], disagree with this finding. Both that study [1] and a meta-analysis in patients with type 2 diabetes [41] have shown no significant differences between accelerometers and pedometers. Consideration must be made in relation to these comparisons being indirect, with such confirmation potentially required through a future 1 versus 1 design.…”
Section: Interpretation Of the Resultsmentioning
confidence: 87%
“…Yet also as demonstrated by the Canadian program SMARTER, its association with a simple medical prescription of a number of daily steps increased PA, and had an impact on the insulin sensitivity of type 2 diabetic patients 38 . Evidence of its direct effectiveness on HbA1C was still not found 39 . The integration of this mechanism might be possible considering that according to studies it seems to be generally accepted by both the patient and the physician 40 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is a metabolic disorder that results in abnormally elevated or sup-pressed blood glucose (BG) values due to the inability or reduced ability of the body to metabolize glucose [1]. Although diet plays an important role in maintaining stable levels of BG, physical activity has the added benefit of preventing an unwanted rise in BG by burning off excess glucose available in the blood stream [2][3][4][5]. Sophisticated motion detectors that are able to distinguish between different classes of activities in real time would provide a much more comprehensive picture of the activity which can be related to a given energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The first and popular tools of self-monitoring are pedometers that were originally designed on 1-axis motion sensors named step counters [4][5][6] or pedometers. These are on-body sensing devices that typically measure the number of "steps" an individual takes in a continuous manner, can only record a limited set of activities (i.e.…”
Section: Introductionmentioning
confidence: 99%